Preparation method of modified Prussian blue sodium battery positive electrode material and positive electrode material prepared by method
By forming a copper -based sulfide covering layer on the surface of Prussian sodium sodium electrode material, the material absorption and side reaction problems are solved, and the circulating performance and magnification of the material are improved.
Patent Information
- Application Number
- CN202411442490.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
AI Technical Summary
The existing Prussian blue sodium electropositive electrode materials have poor rate performance and cycle stability and low Coulomb efficiency due to the crystallization water and lattice vacancy in the structure, easy water absorption, poor electron conductivity and side reactions between the electrode and the electrolyte. and potential polarization is obvious.
A liquid deposition coating process was used to form a copper-based sulfide coating layer on the surface of the Prussian blue sodium electrode cathode material, and the modified material was prepared through steps such as ultrasonic dispersion, hydrothermal reaction, and vacuum drying.
It significantly reduces the water absorption of the material, inhibits electrochemical reaction interface side reactions, improves the interface stability and cycle performance of the material, and enhances the rate performance and Coulombic efficiency.
Smart Images

Figure CN119361630A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion batteries, and specifically relates to a method for coating a copper-based sulfide-modified Prussian blue sodium-ion positive electrode material and a positive electrode material prepared by the method. Background Art
[0002] At present, we are vigorously developing renewable clean energy technologies such as wind energy, solar energy, and tidal energy, and gradually reducing the proportion of traditional fossil energy in the energy supply system. However, this type of renewable clean energy is intermittent and random, and is limited by environmental factors such as climate and geographical location. The converted electricity cannot be stably absorbed by the power grid, which has a great impact on the stability of the power grid. Therefore, it is urgent to develop large-scale advanced energy storage systems to solve the time and space limitations of renewable clean energy generation, smooth out power grid fluctuations, and promote the utilization rate of renewable energy. Compared with existing physical energy storage, chemical energy storage, and electrochemical energy storage technologies, electrochemical energy storage is favored due to its good flexibility, high energy density, and high energy conversion efficiency.
[0003] At present, lithium-ion batteries have achieved rapid development in the field of electrochemical energy storage. However, limited lithium resources and their uneven distribution have caused people to worry about their development prospects in the field of large-scale energy storage. Sodium and lithium elements have similar chemical properties. Their resources are abundant and widely distributed, which makes sodium-ion batteries more advantageous than lithium-ion batteries in some future energy storage applications. However, compared with lithium ions, sodium ions are larger in size and mass, resulting in poor electrochemical performance of sodium-ion batteries. It is necessary to develop sodium-ion battery electrode materials with high energy density and good structural stability to meet the requirements of large-scale energy storage in terms of energy storage capacity, service life and safety.
[0004] The cathode materials of sodium ion batteries mainly include layered and tunnel-type transition metal oxides, polyanionic compounds, and Prussian blue compounds. Prussian blue sodium cathode materials are materials with unique open frameworks and three-dimensional macroporous structures. Their structural characteristics are particularly suitable for the deintercalation and storage of sodium ions. They have the advantages of low cost, easy synthesis, and high theoretical specific capacity. They are very promising cathode materials for sodium ion batteries. However, due to the presence of more crystal water and lattice vacancies in the crystal structure caused by the synthesis of the materials, easy water absorption, poor electronic conductivity, and side reactions between electrodes and electrolytes, Prussian blue sodium cathode materials often have poor rate performance and cycle stability, low Coulomb efficiency, and obvious potential polarization. Therefore, how to improve the structure and interface stability of Prussian blue sodium cathode materials has become a key issue that needs to be solved urgently in academia and industry.
[0005] In order to improve the interfacial stability of Prussian blue sodium positive electrode materials, a layer of compound can be coated on the surface of the material to avoid direct contact between the electrolyte and the Prussian blue sodium positive electrode material, significantly inhibiting the occurrence of electrochemical interface side reactions, thereby improving the cycle performance of the material. CN113921798A, CN115411260A and CN114620758A disclose technical means for coating a layer of oxides such as aluminum oxide, titanium oxide, silicon oxide, zirconium oxide and copper oxide on the surface of Prussian blue sodium positive electrode materials. After the oxide surface coating modification, the water absorption of the Prussian blue sodium positive electrode material is suppressed, and the cycle performance of the material is improved. However, the coated oxide has extremely low electrical conductivity, and wrapping on the surface of the material is not conducive to the transmission of electrons, affecting the rate performance of the material.
[0006] In order to achieve the effect of improving the electrochemical reaction interface stability of the material without affecting the conductivity and rate performance of the material, it is necessary to find a modifying material with stable chemical properties and high conductivity for surface coating modification. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a modified Prussian blue sodium-based positive electrode material, which can solve the problem of reduced conductivity caused by coating the material surface with oxide in the prior art. The method is a liquid deposition coating process with simple process and suitable for large-scale production. The purpose of the present invention is also to provide a copper-based sulfide-coated modified Prussian blue sodium-based positive electrode material prepared by the above method.
[0008] In order to solve the above technical problems, the preparation method of the present invention comprises the following steps: (1) Mixing deionized water and a Prussian blue sodium cathode material and ultrasonically dispersing the mixture for 1 to 6 hours to prepare a suspension A having a solid content of 10 to 70 wt%; (2) Soluble Cu 2+ Add salt to the suspension A obtained in step (1), control the mass ratio of copper element to Prussian blue sodium positive electrode material to be 0.00665-0.0665:1, and stir for 0.5-4h to obtain suspension B; (3) Configure soluble S 2- salt solution, and add it dropwise to the suspension B obtained in step (2) under stirring, and control S 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 0.5-4:1, Cu 2+ With S 2- The molar ratio is 0.5 to 4:1 to obtain suspension C; (4) transferring the suspension C to a reactor and performing a hydrothermal reaction to obtain a precipitate; (5) Washing the precipitate obtained in step (4) with deionized water and ethanol, and vacuum drying the washed precipitate to obtain a copper-based sulfide-coated modified Prussian blue sodium-based positive electrode material.
[0009] In the step (1), the Prussian blue sodium positive electrode material includes one of an iron-based Prussian blue sodium positive electrode material, an iron-manganese-based Prussian blue sodium positive electrode material, an iron-cobalt-based Prussian blue sodium positive electrode material, an iron-nickel-based Prussian blue sodium positive electrode material, and an iron-copper-based Prussian blue sodium positive electrode material.
[0010] In the step (1), the ultrasonic dispersion time is 2 to 5 hours; preferably, the ultrasonic dispersion time is 3 to 4 hours.
[0011] In the step (1), the solid content of the suspension A is 20-60 wt %; preferably, the solid content of the suspension A is 30-40 wt %.
[0012] In the step (2), the mass ratio of copper element to Prussian blue sodium positive electrode material is 0.0133-0.0532:1; preferably, the mass ratio of copper element to Prussian blue sodium positive electrode material is 0.0266-0.0399:1.
[0013] In the step (2), the soluble Cu 2+ The salt includes one of copper chloride, copper nitrate, copper acetate, and copper sulfate; preferably soluble Cu 2+ The salt includes one of copper chloride, copper acetate, and copper sulfate; more preferably soluble Cu 2+ The salt is copper chloride.
[0014] In the step (2), the stirring time is 1 to 3 hours; preferably, the stirring time is 1.5 to 2.5 hours.
[0015] In the step (3), the soluble S 2- The salt includes one of sodium sulfide, sodium thiosulfate, thiourea, ammonium sulfide, and thioacetamide; preferably soluble S 2- The salt includes one of sodium sulfide, sodium thiosulfate, and ammonium sulfide; more preferably, soluble S 2- The salt is sodium sulfide.
[0016] In the step (3), the soluble S 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 1 to 3:1; preferably, the soluble S 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 1.5 to 2.5:1.
[0017] In the step (3), Cu2+ With S 2- The molar ratio is 1 to 3:1; preferably Cu 2+ With S 2- The molar ratio is 1.5 to 2.5:1.
[0018] In the step (3), the stirring speed is 100 to 900 r / min; preferably, the stirring speed is 300 to 700 r / min; more preferably, the stirring speed is 500 to 600 r / min.
[0019] In the step (3), the soluble S 2- The salt solution drop rate is 1-50 ml / min; preferably soluble S 2- The salt solution drop rate is 10 to 40 ml / min; more preferably, soluble S 2- The salt solution dropping speed is 20-30 ml / min.
[0020] In the step (4), the hydrothermal reaction temperature is 120-200°C; preferably, the hydrothermal reaction temperature is 130-180°C; more preferably, the hydrothermal reaction temperature is 140-160°C.
[0021] In the step (4), the hydrothermal reaction time is 5 to 15 hours; preferably, the hydrothermal reaction time is 8 to 14 hours; more preferably, the hydrothermal reaction time is 11 to 13 hours.
[0022] In the step (5), the vacuum drying temperature is 100 to 250°C; preferably, the vacuum drying temperature is 130 to 200°C; more preferably, the vacuum drying temperature is 160 to 180°C.
[0023] In the step (5), the vacuum drying time is 12 to 30 hours; preferably, the vacuum drying time is 15 to 25 hours; more preferably, the vacuum drying time is 19 to 21 hours.
[0024] The present invention also provides a modified Prussian blue sodium-based positive electrode material, which is prepared by the above method; the positive electrode material comprises a Prussian blue sodium-based positive electrode material matrix and a copper-based sulfide coating layer.
[0025] Since a copper-based sulfide coating layer is formed on the surface of the Prussian blue sodium-based cathode material by using a liquid phase deposition coating process, the method provided by the present invention and the obtained modified Prussian blue sodium-based cathode material bring the following beneficial effects: (1) Copper-based sulfides are chemically stable and are extremely insoluble in water. The present invention coats a layer of copper-based sulfide on the surface of the Prussian blue sodium cathode material through a liquid phase deposition coating process, which can isolate the material from direct contact with moisture in the air, reduce its water absorption, and improve the processing performance of the material.
[0026] (2) The presence of the copper-based sulfide coating layer can prevent the Prussian blue sodium cathode material matrix from directly contacting the electrolyte, which can significantly inhibit the occurrence of side reactions at the electrochemical reaction interface, increase the interfacial stability of the material, and thus achieve the effect of improving the material's cycle performance.
[0027] (3) The crystal structure of copper-based sulfides can reversibly deintercalate lithium and sodium, and has a very high theoretical capacity. Therefore, the copper-based sulfide coating can provide additional active sites for sodium ion deintercalation, reduce the irreversible capacity caused by the coating, and improve the coulombic efficiency of the material.
[0028] (4) Copper-based sulfides usually behave as p-type semiconductors with a band gap between 1.2 and 2.4 eV, which makes them have higher conductivity than copper oxide. Coating the surface of the material can improve the electrochemical reaction interface stability of Prussian blue sodium cathode materials while avoiding affecting the conductivity of the material itself, thereby improving the rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The charge and discharge curves of the copper-based sulfide-coated modified iron-manganese-based Prussian blue sodium-based cathode material prepared in Example 1 of the present invention and the iron-manganese-based Prussian blue sodium-based cathode material prepared in Comparative Example 1 at 0.1C.
[0030] Figure 2 This is an X-ray diffraction (XRD) pattern of the copper-based sulfide-coated modified iron-manganese-based Prussian blue sodium-based cathode material prepared in Example 1 of the present invention.
[0031] Figure 3 This is a scanning electron microscope (SEM) image of the copper-based sulfide-coated modified iron-manganese-based Prussian blue sodium-based cathode material prepared in Example 1. (Abstract attached) Figure 4 This is a scanning electron microscope (SEM) image of the iron-manganese-based Prussian blue sodium-based positive electrode material without any treatment in Comparative Example 1 of the present invention.
[0032] Figure 5 This is an electron image collected when performing energy dispersive X-ray spectroscopy analysis on the copper-based sulfide-coated modified iron-manganese-based Prussian blue sodium-based cathode material prepared in Example 1 of the present invention.
[0033] Figure 6 for Figure 5 Energy dispersive X-ray spectroscopy (EDS) of selected areas. DETAILED DESCRIPTION
[0034] In order to make the present invention more obvious and easy to understand, the technical solution of the present invention is further explained below through embodiments in combination with the drawings, but it is not intended to limit the protection scope of the present invention.
[0035] In the present invention, the Prussian blue sodium positive electrode material includes but is not limited to one of an iron-based Prussian blue material, an iron-manganese-based Prussian blue material, an iron-cobalt-based Prussian blue material, an iron-nickel-based Prussian blue material, and an iron-copper-based Prussian blue material. The Prussian blue sodium positive electrode material selected in the embodiment of the present invention is an iron-manganese-based Prussian blue material. The specific synthesis process is as follows: (1) Prepare 100 ml of 0.2 mol / L manganese sulfate solution and sodium ferrocyanide solution using manganese sulfate and sodium ferrocyanide decahydrate as solutes and distilled water as solvent, respectively; (2) Dissolve sodium chloride in 100 mL of distilled water to prepare a solution with a molar concentration of 0.2 mol / L; (3) using a peristaltic pump to add the manganese sulfate solution and sodium ferrocyanide solution dropwise to the sodium chloride solution under magnetic stirring at 70°C at a rate of 2 ml / min to form a milky white suspension. After the addition is completed, the milky white suspension is stirred for 3 hours; (4) After stopping stirring, the obtained suspension was centrifuged to obtain a milky white precipitate, which was washed three times with deionized water and anhydrous ethanol respectively, and then the precipitate was vacuum dried at 120° C. for 12 hours to obtain an uncoated and modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 1
[0036] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 3.5 hours to obtain a suspension A with a solid content of 35wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.0333:1, and copper chloride was added to the suspension A and stirred for 2 hours to obtain a suspension B. 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 2:1, Cu 2+ With S 2- The molar ratio is 2:1, and sodium sulfide is prepared into a soluble S 2- The salt solution was added dropwise to the suspension B at 25 ml / min under stirring at 550 r / min to obtain suspension C. The suspension C was transferred to a reactor and subjected to a hydrothermal reaction at 150°C for 12 h to obtain a precipitate, which was then washed with deionized water and ethanol. The washed precipitate was vacuum dried at 170°C for 20 h to obtain a copper-based sulfide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material.
[0037] During the modification process, Cu in suspension B 2+ With the dripping S 2- S in salt solution 2-The reaction generates copper-based sulfide, which is coated on the surface of the iron-manganese-based Prussian blue sodium-based cathode material in the suspension. After a hydrothermal reaction at 150°C for 12 hours, the crystallinity of the copper-based sulfide coated on the surface of the iron-manganese-based Prussian blue sodium-based cathode material is further improved, which improves the stability of the copper-based sulfide, which is conducive to better achieving the purpose of coating modification to improve the electrochemical performance of the material.
[0038] The copper-based sulfide coated on the surface of the iron-manganese-based Prussian blue sodium-type cathode material is extremely insoluble in water, which can isolate the material from direct contact with moisture in the air, reduce its water absorption, and improve the processing performance of the material. The presence of the copper-based sulfide coating layer can prevent the direct contact between the Prussian blue sodium-type cathode material matrix and the electrolyte, which can significantly inhibit the occurrence of side reactions at the electrochemical reaction interface, increase the interface stability of the material, and achieve the effect of improving the cycle performance of the material. The copper-based sulfide coating layer can provide additional sodium ion deintercalation active sites, reduce the irreversible capacity caused by the coating, and improve the coulombic efficiency of the material. Copper-based sulfide has a relatively high electrical conductivity. Coating it on the surface of the material can improve the electrochemical reaction interface stability of the Prussian blue sodium-type cathode material, while avoiding affecting the electrical conductivity of the material itself, thereby improving the rate performance of the material.
[0039] Figure 1 The first charge and discharge curves of the materials obtained in Example 1 and Comparative Example 1 at 0.1C are shown. It can be seen from the figure that the 0.1C discharge capacity of the material in Example 1 is higher. In addition, the coulomb efficiency of the first charge and discharge of the material obtained in Example 1 is 96%, while the first efficiency of the material in Comparative Example 1 is only 91%, which can indicate that the side reaction between the electrolyte and the interface during the charge and discharge process of the copper-based sulfide modified material is suppressed.
[0040] Figure 2 The X-ray diffraction (XRD) diagram of the copper-based sulfide coated and modified iron-manganese-based Prussian blue sodium-type positive electrode material prepared in Example 1 of the present invention shows that the structure of the material does not change after the copper-based sulfide coating modification, and the main characteristic peaks in the X-ray diffraction (XRD) diagram correspond to the iron-manganese-based Prussian blue sodium-type positive electrode material, indicating that this technical solution will not destroy the structure of the material and cause it to lose its electrochemical activity. A weak copper-based sulfide CuS characteristic peak appears at 31.8°, which indicates that this technical solution successfully forms a copper-based sulfide CuS coating layer on the surface of the Prussian blue sodium-type positive electrode material. Example 2
[0041] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 4 hours to obtain a suspension A with a solid content of 30wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.0266:1, and copper sulfate was added to the suspension A and stirred for 2.5 hours to obtain a suspension B. 2-The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 2.5:1, Cu 2+ With S 2- The molar ratio is 1.5:1, and ammonium sulfide is used to prepare a soluble S 2- The salt solution was added dropwise to the suspension B at 30 ml / min under stirring at 600 r / min to obtain suspension C. The suspension C was transferred to a reactor and subjected to a hydrothermal reaction at 160°C for 11 h to obtain a precipitate, which was then washed with deionized water and ethanol. The washed precipitate was vacuum dried at 180°C for 19 h to obtain a copper-based sulfide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 3
[0042] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 3 hours to obtain a suspension A with a solid content of 40wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.0399:1, and copper acetate was added to the suspension A and stirred for 1.5 hours to obtain a suspension B. 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 1.5:1, Cu 2+ With S 2- The molar ratio is 2.5:1, and sodium thiosulfate is used to prepare a soluble S 2- The salt solution was added dropwise to the suspension B at 20 ml / min under stirring at 500 r / min to obtain suspension C. The suspension C was transferred to a reactor and subjected to a hydrothermal reaction at 140°C for 13 h to obtain a precipitate, which was then washed with deionized water and ethanol. The washed precipitate was vacuum dried at 160°C for 21 h to obtain a copper-based sulfide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 4
[0043] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 5 hours to obtain a suspension A with a solid content of 20wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.0532:1, and copper nitrate was added to the suspension A and stirred for 3 hours to obtain a suspension B. 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 3:1, Cu 2+ With S 2- The molar ratio is 1:1, and thiourea is prepared into a soluble S 2-The salt solution was added dropwise to the suspension B at 10 ml / min under stirring at 700 r / min to obtain suspension C. The suspension C was transferred to a reactor and subjected to a hydrothermal reaction at 130°C for 14 h to obtain a precipitate, which was then washed with deionized water and ethanol. The washed precipitate was vacuum dried at 130°C for 25 h to obtain a copper-based sulfide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 5
[0044] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 2 hours to obtain a suspension A with a solid content of 60wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.0133:1, and copper sulfate was added to the suspension A and stirred for 1 hour to obtain a suspension B. 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 1:1, Cu 2+ With S 2- The molar ratio is 3:1, and thioacetamide is prepared into a soluble S 2- The salt solution was added dropwise to the suspension B at 40 ml / min under stirring at 300 r / min to obtain suspension C. The suspension C was transferred to a reactor and subjected to a hydrothermal reaction at 180°C for 8 h to obtain a precipitate, which was then washed with deionized water and ethanol. The washed precipitate was vacuum dried at 200°C for 15 h to obtain a copper-based sulfide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 6
[0045] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 6 hours to obtain a suspension A with a solid content of 70wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.00665:1, and copper sulfate was added to the suspension A and stirred for 4 hours to obtain a suspension B. 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 0.5:1, Cu 2+ With S 2- The molar ratio is 0.5:1, and sodium sulfide is prepared into a soluble S 2- The salt solution was added dropwise to the suspension B at 1 ml / min under stirring at 900 r / min to obtain suspension C. The suspension C was transferred to a reactor and subjected to a hydrothermal reaction at 200°C for 5 h to obtain a precipitate, which was then washed with deionized water and ethanol. The washed precipitate was vacuum dried at 250°C for 12 h to obtain a copper-based sulfide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 7
[0046] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 1 hour to obtain a suspension A with a solid content of 10wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.0665:1, and copper sulfate was added to the suspension A and stirred for 0.5h to obtain a suspension B. 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 4:1, Cu 2+ With S 2- The molar ratio is 4:1, and sodium sulfide is prepared into a soluble S 2- The salt solution was added dropwise to the suspension B at 50 ml / min under stirring at 100 r / min to obtain suspension C. The suspension C was transferred to a reactor and subjected to a hydrothermal reaction at 120°C for 15 h to obtain a precipitate, which was then washed with deionized water and ethanol. The washed precipitate was vacuum dried at 100°C for 30 h to obtain a copper-based sulfide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material.
[0047] In order to illustrate the necessity of each technical link of the present invention for the beneficial effects, the following comparative examples are implemented. Comparative Example 1
[0048] An iron-manganese-based Prussian blue sodium-based positive electrode material without any treatment was used as Comparative Example 1. Comparative Example 2
[0049] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 3.5 hours to obtain a suspension A with a solid content of 35wt%. The mass ratio of copper element to Prussian blue sodium-based cathode material was controlled to be 0.0333:1, and copper chloride was added to the suspension A and stirred for 2 hours to obtain a suspension B. A NaHCO3 solution was prepared, and the NaHCO3 solution and the soluble Cu in the suspension B 2+ The salt molar concentration ratio is 2:1, Cu 2+ The molar ratio of NaHCO3 is 1:2, and it is added dropwise to suspension B at 25 ml / min under stirring at 550 r / min to obtain suspension C. Suspension C is transferred to a reactor and subjected to hydrothermal reaction at 150°C for 12 h to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is heat treated at 170°C for 20 h under nitrogen as a protective gas to obtain an iron-manganese-based Prussian blue sodium-based positive electrode material with a copper-based oxide surface coated and modified.
[0050] The material prepared by the process of the embodiment and the comparative example is immediately used as an active material to prepare a positive electrode sheet for the assembly test of a sodium ion battery.
[0051] The preparation process of the positive electrode is as follows: the positive electrode is composed of four parts: active material, conductive agent, binder and current collector. Ketjen black is used as the conductive agent, 20mg / ml polyvinylidene fluoride (PVDF) N-methylpyrrolidone (NMP) solution is used as the binder, the active material, conductive agent and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1 and ground into a slurry with suitable viscosity, and then the slurry is evenly coated on the carbon-coated aluminum foil. The coated electrode is placed in a vacuum drying oven at 120°C and dried for 10 hours. After drying, it is punched into a small disc with a diameter of 12mm by a punching machine, and finally placed in a glove box in an argon atmosphere for battery assembly.
[0052] The battery assembly process is as follows: the prepared positive electrode sheet is used as the positive electrode, the metal sodium sheet is used as the negative electrode, the diaphragm is a glass fiber diaphragm, 200 μL of 1 mol / L sodium hexafluorophosphate electrolyte is added, the electrolyte solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1, and 5% fluoroethylene carbonate (FEC) is added to the electrolyte as an additive. The button-type half-cell is assembled in the order of the negative electrode shell, spring, gasket, sodium sheet, diaphragm, positive electrode, and positive electrode shell, and finally packaged using a button-type battery sealing machine.
[0053] The assembled button half-cell adopts constant current charge and discharge mode in the voltage range of 2.0 to 4.0 V to carry out corresponding electrochemical performance tests.
[0054] In addition, in order to test the storage performance of the material, the materials prepared by the process of Example 1 and Comparative Example 1 were exposed to air for 10 hours to prepare electrode sheets and assembled batteries for corresponding electrochemical performance tests. The samples were marked as Example 1-10h and Comparative Example 1-10h, respectively.
[0055]
[0056] The performance of each embodiment and comparative example 2 is better than that of comparative example 1, which shows that the electrochemical properties of the material can be significantly improved by surface coating. By comparison, it can be seen that embodiment 1 has the best electrochemical performance. By comparing the discharge specific capacity of embodiment 1 and comparative example 2, it can be seen that the capacity difference of the material is small at a low discharge rate of 0.1C, but the capacity difference becomes larger at a high rate discharge. At 5C and 10C, the discharge specific capacity of embodiment 1 is 15.3mAh / g and 28.2mAh / g higher than that of comparative example 1, respectively, which shows that the copper-based sulfide-coated modified Prussian blue sodium electrical material prepared by this process scheme has high electrical conductivity. In Example 1 and the samples after being set aside for 10 hours, the difference in discharge capacity at different rates from 0.1C to 10C does not exceed 1 mAh / g, and the difference in retention rate after 1000 cycles at 1C does not exceed 1%; in Comparative Example 1, the difference in discharge capacity at different rates after being set aside for 10 hours is relatively large, and the capacity difference at 10C discharge is as high as 19 mAh / g, and the difference in retention rate after 1000 cycles at 1C is greater than 10%, which indicates that the copper-based sulfide coating modification of Prussian blue sodium cathode materials using the present technical solution inhibits the water absorption of the material, improves the storage stability of the material, and is beneficial to improving the processing performance of the material.
[0057] The 1C cycle 1000-week capacity retention rate of each embodiment is not less than 86%, and the 10C high-discharge capacity is greater than 115 mAh / g, which is better than the comparative example. From these two points of comparison, it can be seen that the copper-based sulfide formed on the surface of the material by the technical solution of the present invention can better improve the conductivity of the material, while avoiding direct contact between the material and the electrolyte, reducing interface side reactions, and thus improving the rate performance and cycle performance of the material.
[0058] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified Prussian blue sodium-based cathode material, characterized in that: The following steps are involved: (1) Mixing deionized water and a Prussian blue sodium cathode material and ultrasonically dispersing the mixture for 1 to 6 hours to prepare a suspension A having a solid content of 10 to 70 wt%; (2) Soluble Cu 2+ Add salt to the suspension A obtained in step (1), control the mass ratio of copper element to Prussian blue sodium positive electrode material to be 0.00665-0.0665:1, and stir for 0.5-4h to obtain suspension B; (3) Configure soluble S 2- salt solution, and add it dropwise to the suspension B obtained in step (2) under stirring, and control S 2- The soluble Cu in salt solution and suspension B 2+ The salt molar concentration ratio is 0.5-4:1, Cu 2+ With S 2- The molar ratio is 0.5 to 4:1 to obtain suspension C; (4) transferring the suspension C to a reactor and performing a hydrothermal reaction to obtain a precipitate; (5) Washing the precipitate obtained in step (4) with deionized water and ethanol, and vacuum drying the washed precipitate to obtain a copper-based sulfide-coated modified Prussian blue sodium-based positive electrode material.
2. The method for preparing the modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (1), the Prussian blue sodium positive electrode material includes one of an iron-based Prussian blue sodium positive electrode material, an iron-manganese-based Prussian blue sodium positive electrode material, an iron-cobalt-based Prussian blue sodium positive electrode material, an iron-nickel-based Prussian blue sodium positive electrode material, and an iron-copper-based Prussian blue sodium positive electrode material.
3. The method for preparing the modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (2), the soluble Cu 2+ The salt includes one of copper chloride, copper nitrate, copper acetate, and copper sulfate.
4. The method for preparing the modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (3), the soluble S 2- The salt includes one of sodium sulfide, sodium thiosulfate, thiourea, ammonium sulfide, and thioacetamide; the stirring speed is 100-900 r / min; S 2- The salt solution dropping speed is 1-50 ml / min.
5. The method for preparing the modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (4), the hydrothermal reaction temperature is 120-200° C., and the hydrothermal reaction time is 5-15 hours.
6. The method for preparing the modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (5), the vacuum drying temperature is 100 to 250° C., and the vacuum drying time is 12 to 30 hours.
7. A modified Prussian blue sodium-based cathode material, characterized in that: The modified Prussian blue sodium-based positive electrode material is prepared by the method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN113921798A
Preparation method of copper oxide modified iron-based Prussian blue positive electrode material
CN114620758A
Gas phase modification method of Prussian blue sodium battery positive electrode material and positive electrode material prepared by same
CN115411260A